Harnessing the power of Raman spectroscopic imaging for ophthalmology - Li, Jing; Yan, Peirao; Li, Yong; Han, Ming; Zeng, Qi; Li, Juan; Yu, Zhe; Zhang, Dongjie; Chen, Xueli (Frontiers in Chemistry, 2023)
Eye diseases can cause great inconvenience to people’s daily life; therefore, it is necessary to study the causes of ocular diseases and related physiological processes. Raman spectroscopic imaging (RSI) is a non-destructive, non-contact detection technique with the advantages of label-free, non-invasive and highly specific. Compared with other mature imaging technologies, RSI can provide real-time molecular information and high-resolution imaging at relatively low cost, making it very suitable for quantitative detection of biological molecules. RSI can reflect the overall situation of the sample, revealing the content distribution of the same substance in different areas of the sample. This review focuses on the recent advances in ophthalmology, with particular emphasis on the powerful use of RSI techniques, as well as its combination with other imaging techniques. Finally, we prospect the wider application and future potential of RSI approaches in ophthalmology.